Operation Cleansweep for Pesticides: PI-48/PI085, 6/2005 - Fishel, Frederick M. (EDIS, 2005)
This fact sheet explains the Florida Department of Agriculture and Consumer Services' Operation Cleansweep for Pesticides. This document is PI-48, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: June 2005. PI-48/PI085: Operation Cleansweep for Pesticides (ufl.edu)